Enhanced aqueous solubility and bioavailability of capsaicin by the preparation of an inclusion complex - Chen, Xiaoyu; Sun, Xun; Ren, Ke; Zhang, Xiaoning; Zhang, Zhirong; Gong, Tao (Arzneimittelforschung, 2010)
To increase the aqueous solubility and poor bioavailability of capsaicin (CAS 404-86-4), in this paper, the effects of hydroxypropyl-β-cyclodextrin (HP-β-CD) on the aqueous solubility and the pharmacokinetic characteristics of capsaicin were investigated. The corresponding inclusion complex of capsaicin/HP-β-CD at the molar ratio of 1:1 was obtained by the method of saturated aqueous solution and characterized by differential scanning calorimetry and X-ray diffractometry. The dissolution rate of capsaicin was significantly increased by the complexation with HP-β-CD, due to its solubilizing activity. The absorption behavior and bioavailability of capsaicin and its complexation were evaluated after their subcutaneous (s. c.) injection in rats. The absorption rates of capsaicin across subcutaneous tissues and its bioavailability were significantly enhanced by the formation of an inclusion complex with HP-β-CD. The present results indicate the potential of utilizing HP-β-CD to improve the subcutaneous absorption and bioavailability of capsaicin.
Keywords: Capsaicin, bioavailability, inclusion complex, pharmacokinetics, subcutaneous absorption; CAS 404-86-4; Hydroxypropyl-β-cyclodextrin